Risk factors for mechanical complications in degenerative lumbar scoliosis with concomitant thoracolumbar kyphosis: does the selection of the upper instrumented vertebra matter? - Weipeng Qiu; Zhuoran Sun; Ze Chen; Siyu Zhou; Qiang Qi; Weishi Li (Journal of Orthopaedic Surgery and Research)
Abstract Background Degenerative lumbar scoliosis (DLS) represents a distinct subset of adult spinal deformity, frequently co-occurring with thoracolumbar kyphosis (TLK) in the sagittal plane. TLK is typically viewed as detrimental in degenerative spinal conditions and has been linked to increased pain severity and a higher prevalence of mechanical complications (MC) as previously reported. The present study aimed to identify the risk factors associated with the development of MC in patients with DLS and concomitant TLK. Methods This study retrospectively included 65 DLS patients with a TLK > 20°. During follow-up, MC events were recorded, and patients were categorized into MC and non-MC groups. Spinopelvic parameters were assessed pre- and post-surgery. The locations of the kyphotic apex (KA) and the upper instrumented vertebra (UIV) were documented. Clinical and radiographic data were compared between the two groups. A multivariate logistic regression model was employed to analyze the independent risk factors for MC. Results Twenty-nine (44.6%) patients developed at least one MC at final follow-up. At baseline, patients in the MC group exhibited lower bone mineral density (P = 0.002), lower distal lumbar lordosis (DLL, P = 0.025), and higher sagittal vertical axis (SVA, P = 0.005). Post-surgery, the KA shifted cranially with an average vertebral displacement of 2.6 ± 1.8. The proportion of UIV located in the postoperative KA area significantly increased (P < 0.001). The MC group had a higher incidence of Roussouly type mismatch (P = 0.023) and UIV located in the KA area (P = 0.003). Multivariate logistic regression analysis revealed that UIV located in the KA area (OR = 3.798, P = 0.043), increased preoperative SVA (OR = 1.017, P = 0.016) and osteoporosis (OR = 6.713, P = 0.007) were independent risk factors for MC. Conclusions The presence of UIV in the KA area, preoperative sagittal imbalance, and osteoporosis were identified as significant risk factors for MC in patients with DLS and concomitant TLK. The spinal morphological characteristics of TLK must be taken into account during surgical planning to prevent placing the UIV within the kyphotic region.